2021
DOI: 10.1002/jssc.202100074
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic ion filtering targeted screening and isolation of anti‐inflammatory iridoid glycosides from Hedyotis diffusa

Abstract: Efficient and targeted screening and isolation of bioactive compounds from complex natural products is still a challenging work. Herein, diagnostic ion filtering based high‐performance liquid chromatography–quadrupole time‐of‐flight−tandem mass spectrometry was firstly developed to screen six main iridoid glycosides from Hedyotis diffusa. Then, online extraction‒high‐speed counter current chromatography was proposed for targeted enrichment and preparative isolation using ethyl acetate/n‐butanol/water (4.5:0.5:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The fragmentation features of nine iridoid glycoside reference standards were analyzed in negative and positive ion modes to generate typical NLs, and then the fragmentation pathways of iridoid glycosides were deduced (Shi et al, 2021; Wu et al, 2010). Iridoid glycosides have no obvious DPIs in MS/MS spectra.…”
Section: Methodsmentioning
confidence: 99%
“…The fragmentation features of nine iridoid glycoside reference standards were analyzed in negative and positive ion modes to generate typical NLs, and then the fragmentation pathways of iridoid glycosides were deduced (Shi et al, 2021; Wu et al, 2010). Iridoid glycosides have no obvious DPIs in MS/MS spectra.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, monotropein strongly inhibited the generation of nitric oxide and TNF-α. Desacetylasperuloside acid had no obvious activity against nitric oxide but had a specific TNF-α inhibitory activity (Shi et al, 2021), which revealed that the hydroxyl group at C-6 could decrease the activity, and the esterification of carboxyl group could enhance the activity (Recio et al, 1994;Viljoen et al, 2012). Furthermore, the major iridoid glycosides from M. officinalis had similar biological activity, enriched by XDA-1 macroporous resin, and the content of monotropein and deacetylasperulosidic acid was 35.9% and 25.9%, respectively.…”
Section: Anti-nociceptive and Anti-inflammatory Effectsmentioning
confidence: 99%
“…However, overwhelming amounts of MS datasets are generated, which makes manual data analysis challenging, especially for achieving MS information of low‐abundance compounds being overwhelmed by major compounds or background noise 20 . To facilitate and simplify post‐acquisition MS data processing, various data mining technologies have been developed with excellent resolution, high sensitivity, outstanding selectivity, and excellent accuracy, such as neutral loss filtering, diagnostic ion filtering, de novo identification, mass defect filtering, isotope pattern filtering, predicted compound screening, and database‐assisted peak annotation 21–24 . To date, only strategies with PMF aglycone‐oriented extraction and mass defect filtering have been established to screen PMFs in Citrus aurantium , Murraya paniculata , Murraya exotica , and C. reticulata Blanco, and their structures were identified by MS/MS spectra with diagnostic product ions 25–29 .…”
Section: Introductionmentioning
confidence: 99%
“…20 To facilitate and simplify post-acquisition MS data processing, various data mining technologies have been developed with excellent resolution, high sensitivity, outstanding selectivity, and excellent accuracy, such as neutral loss filtering, diagnostic ion filtering, de novo identification, mass defect filtering, isotope pattern filtering, predicted compound screening, and database-assisted peak annotation. [21][22][23][24] To date, only strategies with PMF aglycone-oriented extraction and mass defect filtering have been established to screen PMFs in Citrus aurantium, Murraya paniculata, Murraya exotica, and C. reticulata Blanco, and their structures were identified by MS/MS spectra with diagnostic product ions. [25][26][27][28][29] Therefore, it is necessary to develop more data mining methods for the rapid screening and identification of PMFs in natural products.…”
Section: Introductionmentioning
confidence: 99%